The World Bank Legal Review, Volume 4 : Legal Innovation and Empowerment for Development - Cissé, Hassane (Washington, DC: World Bank, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.